PENGARUH PENDEKATAN BERMAIN BOLA BASKET UNTUK MENINGKATKAN MINAT AKTIVITAS FISIK SISWA SEKOLAH MENENGAH PERTAMA - Febriana, Jihan; Fajar Ari Widiyatmoko; Agus Wiyanto (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
The background to this research is because there are problems, namely the lack of interest in physical activity among junior high school students in learning basketball and the lack of variety of models during learning. The aim of this research is to find out the influence of the approach to playing basketball to increase the interest in physical activity of 1st year junior high school students. The research method uses a quantitative approach and uses a Pretest-Posttest Control Group Design. The population in this research was all students in class VIII of SMPN 1 Tahunan and the sample used was 64 students. The instrument used was a questionnaire. From the results of the questionnaire indicator for interest in physical activity for SMPN 1 Annual students, the pretest was 55.7, the posttest was 58.9, in other words, there was an increase of 5.74%. Therefore, the t test results are obtained with a sig value. 0.001 so that providing treatment using a basketball playing approach has a significant influence on increasing the interest in physical activity of 1st Annual Middle School students. The conclusion is that there is an influence of the learning model using a basketball playing approach on increasing the interest in physical activity of 1st Annual Middle School students. Suggestions for teachers are expected to be able to provide variations of games in PJOK learning to increase students' interest and enthusiasm for carrying out activities related to physical activity.